Pharmaceutical and Endocrine Disruptor Compounds in Surface and Wastewater in San Marcos, Texas: Oates et al. (1st November 2017) - Oates, R. P.; Longley, Glenn; Hamlett, Pamela; Klein, David
ABSTRACT: : Water resource recovery facilities (WRRFs) and hospitals are major point sources of pharmaceuticals and endocrine disrupting compounds (EDCs) in aquatic environments. This study investigated the removal efficiencies of 23 known or suspected EDCs through the San Marcos WRRF to determine which treatment process was the most effective at removal. Results from samples collected at the hospital indicate that the hospital discharge is contributing to the concentration of these compounds in the San Marcos wastewater collection system (0.05–140 μg/L concentrations). The most frequently detected compounds in the WRRF influent included acetaminophen, nonylphenol, caffeine, benzophenone, N, N‐diethyl‐m‐toluamide (DEET), bisphenol A (BPA), and triclosan. Comparison of influent and effluent concentrations showed that the San Marcos WRRF is effectively removing (>92%) of these compounds, with the exception of carbamazepine and tris(2‐chloroethyl) phosphate (TCEP). These preliminary results will be used to guide future improvements within the WRRF.